Análise da relação entre fracasso escolar – leitura – alfabetização em uma pesquisa do tipo estado do conhecimento - Silva, Cristiane Freitas Pereira da (2021)
This research is linked to the Postgraduate Program in Education, of the Human and Social Sciences Institute, of the Federal University of Mato Grosso (UFMT) – University Campus of Rondonópolis (PPGEdu/ICHS/UFMT/CUR), in the research line Languages, Culture and Knowledge Construction: historical and contemporary perspectives, bound to the Research Group Alphabetization and School Literacy (ALFALE). The main objective is to analyze how it has been investigated the correlation School Failure – Reading – Literacy, by researchers and postgraduate students in Brazil, from a research of the type state of knowledge taking as locus for the obtainment of data the constant records on the Brazilian Digital Library of Dissertations and Theses (BDTD). It is a research of qualitative nature guided by the Content Analysis (BARDIN, 2011), inside this approach, it was opted for the use of a research of bibliographic nature of the type state of knowledge. For the data gathering with the Brazilian Digital Library of Dissertations and Theses (BDTD), it was used the terms: school failure, reading and literacy in the space advanced search, in the period from 2002 to 2019. At first it was obtained 55 papers, being 42 theses and 13 dissertations. Soon after, we proceeded with the floating reading of the materials, starting with the master's theses and then the doctoral theses, continuing the investigation, contemplating all the steps recommended by the chosen method, with the hypothesis that, when mapping, investigate and knowing what has been produced from academic-scientific knowledge on this subject makes it possible to advance in other research fronts, as well as contributing to the confrontation of school failure. This balance showed that, although these dialogues are not new in our country, there is still much to be debated today. Furthermore, there is still, albeit in a subtle way, a certain culture of blaming the production of school failure, although there are suggestions for possible interventions that minimize the historical and social impacts on the lives of those who suffer this phenomenon, being excluded and marginalized by failure in literacy and lack of appropriation of reading.